Mediated postnuptial agreements and ancillary matters: Surindar Singh s/o Jaswant Singh v Sita Jaswant Kaur [2014] SGCA 37 - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2014)
When the parties in a divorce have, with the benefit of legal counsel, gone through mediation and negotiated an agreement to settle the ancillary issues of maintenance and the division of matrimonial assets, is there any reason for the court to exercise its statutorily conferred discretion to ignore such an agreement or should it seek to uphold it despite objections from one of the parties? Whereas the High Court in this case declined to follow all of the terms in the agreement on the ground that some of them were not just and equitable, the Court of Appeal held that given the context in which the agreement was made, the agreement should not only be given significant weight but conclusive weight and full effect. The reasoning and implications of the Court of Appeal’s decision will be considered in greater detail here.